2019
DOI: 10.1111/codi.14871
|View full text |Cite
|
Sign up to set email alerts
|

The association of age with the clinicopathological characteristics and prognosis of colorectal cancer: a UK single‐centre retrospective study

Abstract: Introduction Colorectal cancer (CRC) is uncommon in patients under the age of 40 years and its association with poor histological features and survival is uncertain. This study aimed to evaluate age‐related differences in clinicopathological features and prognosis in patients diagnosed with CRC. Method A single‐centre retrospective review of all patients diagnosed with CRC between 2004 and 2013 was performed. Patients were stratified into three age groups: (1) 18–40 years, (2) 41–60 years and (3)> 60 years. Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…In views of epidemiology, age has been widely accepted as a major risk factor for sporadic CRC (14). This is consistent with our ndings in the study.…”
Section: Discussionsupporting
confidence: 93%
“…In views of epidemiology, age has been widely accepted as a major risk factor for sporadic CRC (14). This is consistent with our ndings in the study.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have mostly focused on the prognosis of CRC patients, and whether age is an independent factor remains controversial. Some studies reported that young patients with CRC had a worse prognosis than older patients [22][23][24]. Some studies reported the opposite results [25,26], and another study demonstrated that age was not associated with the prognosis of CRC [27].…”
Section: Discussionmentioning
confidence: 99%
“…Even when considering that our study included only patients who underwent surgery, the larger proportion of younger patients compared to other countries remains valid. According to a study conducted in the United Kingdom [ 12 ], about 2.1% of CRC patients are less than 40 years old. In contrast, in Korea, the proportion of CRC patients under 40 years of age is reported to be 6.5% [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the 5-year survival rates of CRC patients have been found to differ in different age groups [7][8][9][10][11]. According to Anele et al [12], patients over the age of 60 years had lower survival rates compared to younger patients in even same stage. It is still unclear whether it was due to differences in tumor biology or because relatively passive treatments were selected for elderly patients.…”
Section: Introductionmentioning
confidence: 99%